if the number is x, then
the positive number, when added to its square (remember, its=posessive and it's is a constraction), equals 42
this can be writen as [tex]x+x^2=42[/tex]
perfect, we need to solve by making one side 0 and then factoring since if ab=0, we can assume and solve for a and b by saying that a=0 and b=0
minus 42 from both sides
[tex]x^2+x-42=0[/tex]
now, either use the quadratic formula or complete the square or factor
I will factor
find what 2 numbers multiply to get -42 and add to get 1 (since the linear coefient is 1 and the constant is -42)
those numbers are -6 and 7
[tex]x^2+x-42=0[/tex]
factor
[tex](x-6)(x+7)=0[/tex]
set each to 0
x-6=0
x=6
x+7=0
x=-7, false since we wanted a positive number
the number is 6